Financial Assistance from Arab countries and Arab regional institutions (Washington D.C : International monetary fund, 1991)
This book review some of the economical development in the Arab world with emphasize to the effects of oil production across the arab spring.
include statistical appendix
asm; 24/01/19
Loans
Keywords: Economical Assistance; Arab countries